EFL Indonesian Learners' Preference on Teachers' Written Feedback Strategies for L2 Writing - Indah Windra Dwie Agustiani; Herasni Yaman; Sri Hartati (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2022)
Feedback is very crucial for students’ learning. It can be used as a supporting source of learning for them by showing the students’ mistakes and errors. Feedback is expected to raise the students awareness of their learning. However, not many students are able to use the feedback given to them. Studies try to explore how to maximise feedback function for the students’ learning. This present study investigated the recognition of students about feedback preference and their response toward teacher feedback for their writing. An EFL class at the tertiary level comprising 28 learners had participated in this study. The participants were required to fill the questionnaire. The data were analysed by using percentage analysis. The data revealed that Indonesian EFL learners prefer the direct corrective feedback for their writing. The majority of the students confirmed that feedback is crucial for their writing progress. However, the data showed that more than half of the students’ responses toward feedback given admitted that they sometimes revised their writing although they were not assigned to submit a revision. Therefore, this study suggested diagnosing students’ teacher Corrective Feedback strategies as the initial step for given feedback procedure as one of the ways to respect students’ learning style or strategies.